EVALUATION OF PAVEMENT CONDITIONS AND MAINTENANCE WORKS FOR ROAD NETWORK IN SAUDI ARABIA - Bardeesi, Mohamad Wajdi; Attallah, Youssef (European Scientific Journal, ESJ, 2015)
An effective pavement management system depends on reliable, accurate, and complete information. Having quality pavement management data is directly linked to the ability of the pavement management system to contribute to the development of reasonable and reliable recommendations and decisions regarding an agency’s pavement network. In this study, historical data of pavement distresses and pavement conditions on the main and secondary road network of Saudi Arabia were collected. These data were categorized, processed, and analyzed. These data have been employed to generate prediction of pavement distresses and conditions evaluation for the Saudi Arabia Urban Road Network. Throughout the study, the most common types of pavement distresses on road network of KSA have been identified. Also, the maintenance programs and priorities have been analyzed. The current computer software for pavement management system in KSA were studied and evaluated.